Selective swelling of electrospun block copolymers: From perforated nanofibers to high flux and responsive ultrafiltration membranes - Shi, X; Xu, Z; Huang, C; Wang, Y; Cui, Z (American Chemical Society, 2018)
This work is devoted to the development of high-flux ultrafiltration membranes using electrospun nanofibers of amphiphilic block copolymers (BCPs) of polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) as building blocks. When soaked in hot ethanol, the solid as-spun BCP fibers are progressively transformed into three-dimensionally perforated fibers with increasing porosities with rising degrees of swelling, which ended up with the equilibrated morphology of spherical micelles. The BCP nanofibers are collected on macroporous substrates and subjected to heating to convert loosely stacked fibers to dense and continuous films. Subsequent swelling in hot ethanol leads to robust composite membranes with nanoporous BCP selective layers tightly adhered to the substrates. Filtration performances of the composite membranes can be conveniently modulated by electrospinning durations. The water permeabilities are as high as 6100 L m–2 h–1 bar–1, which is ∼10–35 times higher than that of commercial membranes with similar rejections. Moreover, with the surface enrichment of P2VP chains the membranes exhibit a strikingly sharp pH-dependent water permeability switchable in the largest amplitude ever reported for multiple cycles. Electrospun fibers can be promising building materials to produce a wide range of membranes with 3D interconnected nanoporosities which also show great potential in separation and biomedical applications.